Emotional literacy in EFL classes: The relationship between teachers' trait emotional intelligence level and the use of emotional literacy strategies. (November 2018) - Kliueva, Ekaterina; Tsagari, Dina
Abstract: This study investigates the relationship between the levels of trait emotional intelligence (trait EI) of teachers of English as a Foreign Language (EFL) and the teaching strategies they use in the classroom to develop students' emotional literacy (EL). It also examines the influence of factors such as teaching experience and class size on teachers' choice of EL strategies. The study used a mixed methods design, first administering questionnaires to EFL teachers (N = 102) within Cyprus and locations outside the country, followed by in-depth interviews with a smaller number of respondents (N = 11). Overall, the questionnaire results indicated a correlation between teachers' trait EI and teaching practices. Furthermore, the content analysis of the interviews, showed that the level of educational sector (school vs university) plays a significant role in the use of these strategies and identified areas for improvement. The results form the basis for recommendations for an EL training program targeting the promotion of EL in the EFL classroom.